The evil behind fast fashion : awareness of sustainable practices and purchasing behaviors - Santos, Inês de Távora Barroco e Moreira dos (2020)
Sustainability is one of the most concerning topics across several industries. The lack of control over supply chains binds the awareness level of companies on their actual impact when it comes to unsustainable practices. The fashion industry is one of the most affected by this lack of control. It is a traditionally opaque industry in terms of value chain and sourcing and has a major environmental impact. The main objective of this study is to understand into what extend the level of consumer awareness and perception across multiple dimensions impacts the purchasing decision and the willingness to purchase of sustainable fashion items. This study also explores whether there is a significant difference between the motivations to purchase and the willingness to purchase sustainable fashion products. Two binary logistic models where developed and relevant differences were found. In the purchasing stage, consumers were found to be affected by the marketing and communication of sustainable fashion products and their perception of the product characteristics. In the consideration stage, consumers were affected by general awareness on sustainable fashion practices. It was also concluded that the self-concern for the environment plays a fundamental role in both stages. This study aims to allow corporations to understand which dimensions they should take into consideration to attract and convert sustainable fashion consumers. Brands have the power to choose whether they want to lead this inevitable revolution or if they want to be led by it.